THE EFFECT OF SOURSOP (ANNONA MURICATA L.) ESSENTIAL OILS ON VIABILITY CELLS: AN IN-VITRO STUDY - Rahman, Friska Ani; Naday, Qotru Al; Utami, Trianna Wahyu (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Development of new preventive agents for dental caries is needed. One of the candidates for preventive agents from natural products is Soursop leaf. The present study aimed to determine the effect of Soursop leaf oil on the cultured epithelial and fibroblast cells.Methods: In this experimental study, Soursop leaf essential oils were provided, and their eï¬€ect was discovered on epithelial and fibroblast cells line using MTT assay. The MTT assay was conducted to measure the activity of enzymes that reduce MTT and switch it to formazan dye creating a purple colour. Using a microplate reader, the optical density was measured at 550 nm and the absorbance value directly represented relative cell numbers.Results: Data compilation and analysis were done using one-way analysis of variance. Soursop leaf essential oils exhibited variable noxious eï¬€ects on cultured cells. The present study shows that epithelial cell death was less than 30% at the concentration 2.5 Âµl/ml while the percentage of fibroblast cell death was less than 30% at smaller concentrations of 1.25 Âµl/ml. Through an increase in the concentration of Soursop leaf essential oils, the toxicity of these materials substantially increased (p<0.05)Conclusion: Soursop leaf essential oils at certain concentrations may cause epithelial and fibroblast cell death.